Worst-case spatial correlation length in probabilistic slope stability analysis. Issue 1 (29th March 2018) - Zhu, D.; Griffiths, D. V.; Fenton, G. A.
Abstract : This note investigates the reliability of undrained slopes by the random finite-element method. The focus of this note is on the worst-case spatial correlation length, namely the correlation length at which the probability of slope failure reaches a maximum. It is shown that the worst-case phenomenon is most pronounced when the mean factor of safety is relatively low or the coefficient of variation is relatively high. Knowledge of the worst-case spatial correlation length is valuable, as it can be employed for conservative design in the absence of substantial soil field data.